2017
DOI: 10.3892/etm.2017.4700
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of a cloacal exstrophy variant as urorectal septum malformation in a fetus by ultrasound: A case report

Abstract: Abstract. Cloacal exstrophy variants are comprised of a wide range of characteristics, of which there are four primary features, including omphalocele, bladder exstrophy, an imperforate anus and spina bifida. The existing literature regarding the differential diagnosis from alternative urinary diseases prenatally are limited. If the bladder is present, defects in the ventral wall may not be visualized with prenatal ultrasound in certain conditions, including oligohydramnios, and differential diagnosis from uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[ 7 ] The characteristics of cloacal exstrophy variants are similar to those of URSMS, which comprise a wide range of disorders with 4 primary features: Omphalocele, bladder exstrophy, an imperforate anus, and spina bifida. [ 8 ] So autopsy is helpful for us to identify them. In addition, URSMS have similar abnormal overlap with the vertebral defects, anal atresia, tracheo-esophageal fistula, renal defects, and radial dysplasia (VATER).…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] The characteristics of cloacal exstrophy variants are similar to those of URSMS, which comprise a wide range of disorders with 4 primary features: Omphalocele, bladder exstrophy, an imperforate anus, and spina bifida. [ 8 ] So autopsy is helpful for us to identify them. In addition, URSMS have similar abnormal overlap with the vertebral defects, anal atresia, tracheo-esophageal fistula, renal defects, and radial dysplasia (VATER).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal obstruction is a malformation that is rarely associated with CE, and only four cases have been reported to date. 2,12,14,15 We speculate that the ruptured omphalocele induced intestinal adhesion, resulting in a disruption of peristaltic movement and secondary, if not complete, intestinal obstruction. The cause of intrauterine fetal death, in this case, remains unknown; however, we speculate that factors related to the umbilical cord played a major role because the umbilical cord severely adhered to the eviscerated intestines, and no anomalies of vital organs, including those of the cardiovascular system, were present.…”
Section: Present Casementioning
confidence: 91%
“…1,2 The cardinal findings of classic CE are an infraumbilical abdominal wall defect mostly with omphalocele, exstrophy of the ileocecal area with prolapsed terminal ileum, flanked by two exstrophied hemibladders, ambiguous external genitalia and an imperforate anus. 3 There have been many reports regarding the prenatal diagnosis of CE since the first report by Meizner et al [4][5][6][7][8][9][10][11][12][13][14][15] However, the largest study on the prenatal diagnosis of CE reported that accurate diagnosis was mostly unsatisfactory, with a rate as low as 17% (1 of 6) 5 and fetal diagnosis remains a challenge. We present a case of classic CE, observed longitudinally from 17 to 30 weeks' gestation, using ultrasonography and magnetic resonance imaging (MRI), and discuss clues for the correct prenatal diagnosis of CE and potential pitfalls, together with a review of the literature.…”
Section: Introductionmentioning
confidence: 99%